Fusobacterium nucleatum Alters Atherosclerosis Risk Factors and Enhances Inflammatory Markers with an Atheroprotective Immune Response in ApoE(null) Mice. - Irina M Velsko (PLoS ONE, 2015)
The American Heart Association supports an association between periodontal disease (PD) and atherosclerotic vascular disease (ASVD) but does not as of yet support a causal relationship. Recently, we have shown that major periodontal pathogens Porphyromonas gingivalis and Treponema denticola are causally associated with acceleration of aortic atherosclerosis in ApoEnull hyperlipidemic mice. The aim of this study was to determine if oral infection with another significant periodontal pathogen Fusobacterium nucleatum can accelerate aortic inflammation and atherosclerosis in the aortic artery of ApoEnull mice. ApoEnull mice (n = 23) were orally infected with F. nucleatum ATCC 49256 and euthanized at 12 and 24 weeks. Periodontal disease assessments including F. nucleatum oral colonization, gingival inflammation, immune response, intrabony defects, and alveolar bone resorption were evaluated. Systemic organs were evaluated for infection, aortic sections were examined for atherosclerosis, and inflammatory markers were measured. Chronic oral infection established F. nucleatum colonization in the oral cavity, induced significant humoral IgG (P=0.0001) and IgM (P=0.001) antibody response (12 and 24 weeks), and resulted in significant (P=0.0001) alveolar bone resorption and intrabony defects. F. nucleatum genomic DNA was detected in systemic organs (heart, aorta, liver, kidney, lung) indicating bacteremia. Aortic atherosclerotic plaque area was measured and showed a local inflammatory infiltrate revealed the presence of F4/80+ macrophages and CD3+ T cells. Vascular inflammation was detected by enhanced systemic cytokines (CD30L, IL-4, IL-12), oxidized LDL and serum amyloid A, as well as altered serum lipid profile (cholesterol, triglycerides, chylomicrons, VLDL, LDL, HDL), in infected mice and altered aortic gene expression in infected mice. Despite evidence for systemic infection in several organs and modulation of known atherosclerosis risk factors, aortic atherosclerotic lesions were significantly reduced after F. nucleatum infection suggesting a potential protective function for this member of the oral microbiota.